The Legal Certainty of Murabahah Contracts in Buying a House - Danu Pratama; Sri Kusriyah; R. Sugiharto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The purpose of this research is to analyze: 1) Implementation of Murabahah contract in buying and selling houses through the Himalayan Puncak Abadi Sharia Cooperative in Palangka Raya City. 2). Legal certainty of Murabahah contracts in buying and selling houses through the Himalayan Puncak Abadi Sharia Cooperative in Palangka Raya City. The approach method used in discussing this research problem is a sociological juridical approach. The research specifications used are descriptive analytical research. This type of data uses primary data and secondary data. The data analysis method used in this research is qualitative analysis.The results of the study were concluded: 1) The implementation of the Murabahah contract in buying and selling houses through the Himalayan Puncak Abadi Sharia Cooperative in Palangka Raya City was started by using the principle of 5C financing analysis and went through several stages. namely the submission of an application by completing the required documents, checking the completeness of the documents, analyzing the feasibility of the financing proposal, approval or rejection of the results of the analysis through the financing committee binding with a notary deed. The Himalayan Puncak Abadi Sharia Cooperative in Palangka Raya City in resolving problematic financing can be overcome by means of qadhi, tahkim, and al-islah. 2) The legal certainty of the Murabahah contract in the sale and purchase of houses through the Himalayan Puncak Abadi Sharia Cooperative in Palangka Raya City can be realized because it is carried out by a notarial deed. The mortgage deed made with a notary deed can provide legal certainty for the parties. Based on the theory of legal certainty, the Murabahah contract is a natural legal certainty contract, which is a type of business transaction contract that has certainty of profits and income both in terms of amount and in terms of delivery, each party involved can predict the payment or payment time.